Athletic movement skills training for sports performance - Brewer, Clive (Human Kinetics, 2017)
The unifying theme of every elite athlete and every spectacular performance is movement. It's the basis for what is recognised as athleticism, the foundation for athletic skill and an essential ingredient for excellence. Setting a new standard for athletic assessment and development, this authoritative guide presents proven protocols for evaluating, correcting, training and translating athletic movement into athletic dominance. Hundreds of photo sequences and illustrations depict how to refine and perfect speed, agility, strength and power-related movements and skills.